Aksjologiczny wymiar reportażu Mirosława Kuleby "Szamil Basajew. Rycerski etos a powinność żołnierska" = Axiological dimension of Mirosław Kuleba?s reportage "Szamil Basajew. Knight`s ethos and the soldier`s duty" - Tomicka, Aleksandra (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Literary reportage is considered the belles-lettres genre. It tells about events the author witnessed or participated in. Reportage dealing with the subject of war has a special place due to the determination of the reporter undertaking such a task. Mirosław Kuleba participated in the Russian-Chechen wars and decided to describe what he saw, experienced and felt, i.a., in the book Szamil Basajew. "Knightly ethos and soldier`s duty".
Keywords: Kuleba, Mirosław (1958- ); Czeczenia; wojna rosyjsko-czeczeńska; wartości; Basajew, Szamil (1965-2006); Herbert, Zbigniew (1924-1998); Chechnya; Russian-Chechen war; values